Determination of selenium in bovine milk in natura from Ceará - Brazil (Research, Society and Development, 2021)
Selenium is essential to human health. Among the foods considered to be a source of selenium are Brazilian nuts, meat, eggs, milk and others, varying according to the geographical area where they are grown or raised. Data on Se in foods grown, processed and marketed in Brazil are absent in Brazilian food composition tables. The aim of the study was to determine the selenium concentration in bovine milk in natura produced in Ceará, Northeast region of Brazil. This is an experimental research, where samples were collected in municipalities of the main milk basins of Ceará. The selenium concentrations were determined by Hydride Generation Atomic Absorption Spectrophotometry coupled to a quartz cell. The moisture, ash and protein contents were analyzed according to the Association of Official Analytical Chemists (1980) methodology, the lipid content by Soxhlet method and the amount of carbohydrates was calculated by difference.  The mean selenium, moisture, ash, protein, lipid and carbohydrate concentrations of fresh bovine milk were 2.9 µg/100mL, 89.0 mg/100mL, 0.6 mg/100mL, 2.9 mg/100mL, 3.6 mg/100mL and 4.0 mg/100mL, respectively. The concentration of selenium in fresh bovine milk ranged from 0.1-9.0 µg/100mL, being higher in some locations compared to other locations in Brazil and worldwide, which may contribute to the consumption of this mineral by the population of the state.